Pembentukan Kader Juru Pemantau Jentik (JUMANTIK) pada Kader Kesehatan di Wilayah Kerja Puskesmas Pagar Agung Kecamatan Lahat, Indonesia Tahun 2023: The Volunteer of Larval Mosquito Monitor (JUMANTIK) Among Health Center Working Area of Pagar Agung, Lahat District, Indonesia 2023 - Somad, Abdul; Detiana, Detiana; Lusiana, Lusiana; Wibowo, Wahyu Dwi Ari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Dengue hemorrhagic fever, or DHF, is a common disease affecting many countries worldwide, particularly in Southeast Asia and the Western Pacific. It is estimated that there are 100–400 million infections annually. Although there is no specific treatment for this virus, controlling mosquito vectors remains the primary focus in controlling its spread. The formation of mosquito surveillance cadres is a crucial strategy in reducing DHF cases by monitoring breeding sites of Aedes aegypti mosquitoes. Training for these cadres and clean village activities are vital for enhancing public knowledge and awareness of DHF prevention. These activities demonstrate that education and training increase the knowledge and participation of mosquito surveillance cadres. Therefore, the formation of mosquito surveillance cadres and practical training are critical steps in the efforts to prevent and control DHF.